First experimental comparison between the Cartesian and the Lissajous trajectory for magnetic particle imaging. (5th April 2017) - Werner, F; Gdaniec, N; Knopp, T
Abstract: Magnetic particle imaging (MPI) is a quantitative imaging modality that allows us to determine the distribution of superparamagnetic nanoparticles. Sampling is achieved by moving a field-free point (FFP) along a specific trajectory through the volume of interest. The magnetic material that lies along the path or in the close vicinity of the FFP changes its magnetization and induces a voltage in the surrounding receiver coils. Various trajectories for the FFP are conceivable, but most experimental MPI scanners either use a Cartesian or a Lissajous sampling trajectory. For the first time, this study compares both sampling methods experimentally using an MPI scanner that allows us to implement both sampling patterns. By default, the scanner is capable of scanning 2D and 3D field of views using a Lissajous trajectory. But since it also has a 1D mode, it is possible to perform Cartesian measurements by shifting the 1D scan line in a perpendicular direction to the FFP movement using the focus field. These line scans are jointly reconstructed to obtain a 2D image. In a further step, the unidirectional Cartesian trajectory is improved by interchanging the excitation and the focus-field direction leading to a bidirectional Cartesian trajectory. Our findings reveal similar results for the bidirectional Cartesian and Lissajous trajectory concerning the overall image quality and sensitivity. In a more detailed view, the bidirectional Cartesian trajectory achieves a slightly higher spatial center resolution, whereas the Lissajous trajectory is more efficient regarding the temporal resolution since less acquisition time is needed to reach an adequate image quality.